Root Locus Based Autopilot PIDâs Parameters Tuning for a Flying Wing Unmanned Aerial Vehicle - Fendy Santoso; Ming Liu (Journal of Engineering and Technological Sciences, 2008)
This paper depicts the applications of classical root locus based PID control to the longitudinal flight dynamics of a Flying Wing Unmanned Aerial Vehicle, P15035, developed by Monash Aerobotics Research Group in the Department of Electrical and Computer Systems Engineering, Monash University, VIC, Australia. The challenge associated with our UAV is related to the fact that all of its motions and attitude variables are controlled by two independently actuated ailerons, namely elevons, as its primary control surfaces along with throttle, in contrast to most conventional aircraft which have rudder, aileron and elevator. The reason to choose PID control is mainly due to its simplicity and availability. Since our current autopilot, MP2028, only provides PID control law for its flight control, our design result can be implemented straight away for PID parameters' tuning and practical flight controls. Simulations indicate that a well-tuned PID autopilot has successfully demonstrated acceptable closed loop performances for both pitch and altitude loops. In general, full PID control configuration is the recommended control mode to overcome the adverse impact of disturbances. Moreover, by utilising this control scheme, overshoots have been successfully suppressed into a certain reasonable level. Furthermore, it has been proven that exact pole-zero cancellations due to derivative controls in both pitch and altitude loop to eliminate the effects of integral action -contributed by open loop transfer functions of elevon-average-to-pitch as well as pitch-to-pitch-rate- is impractical